2016
DOI: 10.1016/j.bmcl.2015.11.098
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of 6,7-dihydropyrazolo[1,5- a ]pyrazin-4-one derivatives as a novel series of mGlu 5 receptor positive allosteric modulators with efficacy in preclinical models of schizophrenia

Abstract: As part of our efforts to identify a suitable back-up compound to our recently disclosed mGlu5 positive allosteric modulator (PAM) clinical candidate VU0490551/JNJ-46778212, this letter details the investigation and challenges of a novel series of 6,7-dihydropyrazolo[1,5-a]pyrazin-4-one derivatives. From these efforts, compound 4k emerged as a potent and selective mGlu5 PAM displaying overall attractive in vitro (pharmacological and ADMET) and PK profiles combined with in vivo efficacy in preclinical models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Numerous studies have described D2/D3 antagonist-induced decreases in operant responding for reward (Harrison et al 1997 ; Heath et al 2015 ; Froger-Colléaux and Castagné 2016 ). Anti-impulsive effects of atomoxetine have also been widely observed in both rodents and humans tested on a variety of cognitive paradigms (Blondeau and Dellu-Hagedorn 2007 ; Navarra et al 2008 ; Robinson et al 2008 ; Paterson et al 2011 ; Fernando et al 2011 ; Baarendse and Vanderschuren 2011 ; Robinson 2012 ; Chamberlain et al 2006 , 2007 ; Bari et al 2009 ; Tomlinson et al 2014 ).The mGlu 5 R PAM, ADX47273, has been observed to reduce the number of impulsive responses in normal healthy rats in the 5-CSRTT (Liu et al 2008 ; Isherwood et al 2015 ), and RO4938581, as well as several mGlu 5 R PAMs, has been demonstrated to reduce hyperactivity observed in models of NMDAr antagonist or psychostimulant administration (Schlumberger et al 2010 ; Bartolomé-Nebreda et al 2013 ; Conde-Ceide et al 2016 ; Ballard et al 2009 ; Redrobe et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have described D2/D3 antagonist-induced decreases in operant responding for reward (Harrison et al 1997 ; Heath et al 2015 ; Froger-Colléaux and Castagné 2016 ). Anti-impulsive effects of atomoxetine have also been widely observed in both rodents and humans tested on a variety of cognitive paradigms (Blondeau and Dellu-Hagedorn 2007 ; Navarra et al 2008 ; Robinson et al 2008 ; Paterson et al 2011 ; Fernando et al 2011 ; Baarendse and Vanderschuren 2011 ; Robinson 2012 ; Chamberlain et al 2006 , 2007 ; Bari et al 2009 ; Tomlinson et al 2014 ).The mGlu 5 R PAM, ADX47273, has been observed to reduce the number of impulsive responses in normal healthy rats in the 5-CSRTT (Liu et al 2008 ; Isherwood et al 2015 ), and RO4938581, as well as several mGlu 5 R PAMs, has been demonstrated to reduce hyperactivity observed in models of NMDAr antagonist or psychostimulant administration (Schlumberger et al 2010 ; Bartolomé-Nebreda et al 2013 ; Conde-Ceide et al 2016 ; Ballard et al 2009 ; Redrobe et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…d -Amphetamine hemisulfate was obtained from Sigma-Aldrich. All mGlu 5 PAMs were synthesized in house at Vanderbilt University, and detailed methods can be found in the following papers or patents: VU0419372/WO 2012092539; VU0408899, VU0409551, VU0415133/WO 2012078817; VU0419832/WO 2012083224; VU0447256/US 20130345203; VU0455651/WO 2012083224; VU0462807; VU0464042/US 20130345204; VU0464075/US 20130345204; VU0360172 ( N -cyclobutyl-6-[2-(3-fluorophenyl)­ethynyl]-3-pyridinecarboxamide) …”
Section: Methodsmentioning
confidence: 99%
“…A number of mGlu 5 PAMs have demonstrated efficacy in rodent models used to predict antipsychotic efficacy and the treatment of cognitive disturbances ( Kinney et al, 2003 ; Lecourtier et al, 2007 ; Liu et al, 2008 ; Conn et al, 2009 ; Stefani and Moghaddam, 2010 ; Vardigan et al, 2010 ; Gastambide et al, 2013 ; Horio et al, 2013 ; Nicoletti et al, 2019 ). However, one caveat of mGlu 5 PAMs includes excitotoxicity mediated by the enhanced NMDAR activity, as high doses of mGlu 5 receptor PAMs have been shown to induce seizures and neurotoxicity in rodents ( Parmentier-Batteur et al, 2014 ; Rook et al, 2015 ; Conde-Ceide et al, 2016 ). To circumvent these adverse side effects, biased mGlu 5 receptor PAMs have been developed to amplify receptor function without recruiting NMDA receptors ( Rook et al, 2013 , 2015 ).…”
Section: Potential Of Allosteric Modulators Of Metabotropic Glutamate...mentioning
confidence: 99%